(untitled) (Research, Society and Development, 2021)
Nuclear technology is the manipulation of ionizing radiation in a controlled way for application in various areas, such as in the area of health, in the generation of electricity by nuclear power plants, in industry, agriculture, environment among others. However, most beneficial and essential applications of nuclear technologies are still unknown and stereotyped by the population. Therefore, scientific dissemination is necessary for society’s awareness of this subject. The present work aimed to disseminate and raise awareness about nuclear technologies and their relationship with the Sustainable Development Goals of the United Nations. Thus, a questionnaire was constructed and applied to trace the profile of the public to be reached, followed by the creation of a profile on social media, called Nucleotiza, to clarify and disseminate the benefits and importance of nuclear technologies. Strategies of scientific dissemination and communication were elaborated in order to dialogue with the non-nuclear public in a clear and simple way, such as lectures for elementary, high school and undergraduate students. Nucleotiza has reached national and international followers from 24 countries and 250 cities, 24 Brazilian states, approximately 100 cities in the state of Minas Gerais, 134 cities in the southeast region and 183 Brazilian cities counted in 2018. The methodology constructed and determined for the work proved to be efficient and applicable in other scientific dissemination and awareness studies.